Studi Kritis Terhadap Pemahaman Fahmi Basya Terkait Dengan Ayat-Ayat Negeri Saba - Ahmad Fudoli Zaenal Arifin; Hasan Bisri; Dadang Darmawan (Khazanah Theologia, 2020)
Criticism is something that must be built in the scientific world. Because, in science there is no such thing as a definite truth. Criticism here to bring it in the right direction. Especially about the story of the past contained in the Qur'an. A story that is explained in it contains truth, lessons and teachings evidently undeniable for all creatures of Allah, for the happiness of the world and the hereafter. This study uses qualitative research in the form of library research, the author uses the approach of the theory of the Qur'an and Interpretation and the theory of Diltheiy thinking and interpretive writing ideas in Indonesia. Meanwhile, the collection of data by means of documentation, namely the book Indonesia Negeri Saba'by Fahmi Basya and also taken from various related sources. Furthermore, the analysis is done by reading and examining Fahmi Basya's understanding writing, which is written in his book. In summary, Fahmi Basya confirmed 14 comparative accounts of Indonesia and Yemen based on the Qur'an and 53 scientific facts which he discovered that Indonesia was the State of Saba'. Fahmi Basya's understanding is very contrary to the commentators at least caused by two problems. Finally, Fahmi Basya wants to prove that the State of Saba 'in the Qur'an in Indonesia. Based on the study of Fahmi Basya's understanding it was found that Fahmi Basya was not an expert in the field of the Qur'an and Tafsir. So, when he understands the Qur'an and reveals the results of his research in the community it needs to be reviewed. Seeing with the scientific viewpoints of the Qur'an, Fahmi Basya's interpretation seems to match his discoveries with the Qur'anic Verses. And forcing all that can be matched look for verses of the Qur'an.